Karakterisasi Cendawan pada Tanah Serpentin Daerah Mandiangin Kabupaten Banjar - Witiyasti Imaningsih (Bioscientiae, 2011)
Serpentine soil is the land that is characterized by many heavy metal content. Three (3) genera of fungi were isolated from serpentine soil Mandiangin. Aspergillus genus with 4 species, 3 species of Penicillium and Trichoderma (2 species). Mandiangin serpentine soil areas containing nickel and chromium by an average of 3630 ug / g dry weight of soil and the average chromium content reached 828.73 ug / g dry weight soil.